Observation of photon polarization in the b→sγ transition - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; et al. (Physical review letters, 2014)
This letter presents a study of the flavor-changing neutral current radiative B±→K±π∓π±γ decays performed using data collected in proton-proton collisions with the LHCb detector at 7 and 8 TeV center-of-mass energies. In this sample, corresponding to an integrated luminosity of 3 fb−1, nearly 14 000 signal events are reconstructed and selected, containing all possible intermediate resonances with a K±π∓π± final state in the [1.1,1.9] GeV/c2 mass range. The distribution of the angle of the photon direction with respect to the plane defined by the final-state hadrons in their rest frame is studied in intervals of K±π∓π± mass and the asymmetry between the number of signal events found on each side of the plane is obtained. The first direct observation of the photon polarization in the b→sγ transition is reported with a significance of 5.2σ.